Acetylcholine-induced ex vivo ATP release from the human nasal mucosa. Issue 4 (August 2017) - Koizumi, Hiroki; Ikezaki, Shoji; Ohbuchi, Toyoaki; Do, Ba Hung; Hohchi, Nobusuke; Kawaguchi, Rintaro; Kitamura, Takuro; Suzuki, Hideaki
Abstract: Objective: The present study aimed at investigating ATP release in response to acetylcholine (Ach) and pharmacologically elucidating the intracellular signal transduction pathway of this reaction in an ex vivo experiment. Methods: The inferior turbinate mucosa was collected from 21 patients with chronic hypertrophic rhinitis who underwent endoscopic turbinectomy. The mucosa was shaped into a filmy round piece, and incubated with chemical(s) in Hank's balanced salt solution for 10 min. After incubation, the ATP concentration was measured by a luciferin-luciferase assay. Results: The baseline release of ATP without stimulus was 57.2 ± 10.3 fM. The ATP release was significantly increased by stimulation with 100 μM Ach. The Ach-induced ATP release was completely inhibited by removing extracellular Ca 2+ . Significant inhibition of the Ach-induced ATP release was also observed by the addition of 1 μM atropine, 40 μM 2-APB, 10 μM CBX, and 100 μM PPADS, whereas 30 nM bafilomycin A1 did not affect the ATP release. Conclusion: These results indicate that the Ach-induced ATP release from the human nasal mucosa is dependent on the pannexin-1 channel and purinergic P2X7 receptor, suggesting that these two molecules constitute a local autocrine/paracrine signaling system in the human nasal epithelium.